Strain profile, electronic band structure and optical gain of self-assembled Ge quantum dots on SiGe virtual substrate - Bose, Sumanta (2014)
Group IV (Si, Ge, Sn) alloys are promising materials for future optoelectronic devices. Their compatibility with Si technology would allow us to engineer novel growth techniques and bandgap engineering methods to obtain direct band gap materials [1]. Other alloy compositions could allow wider wavelength range [2] which can revolutionize the photonics industry - leading to new design of LEDs, photodetectors, laser diodes and electro optical modulators.